Strategi Guru Mengaji dalam Meningkatkan Kemampuan Membaca Al-Qur’an di Mushala Jihadul Ihsan Jorong Balai Oli Nagari Jawi Jawi Guguk - Eliska, Mizia; Wiza, Rahmi (YASIN, 2025)
This study is motivated by the increasing Qur’anic reading proficiency of students, as reflected in various achievements in Musabaqah Tilawatil Qur’an (MTQ) competitions, particularly at Mushala Jihadul Ihsan, Jorong Balai Oli, Nagari Jawi Jawi Guguk. The study aims to explore the strategies employed by Qur’an teachers to enhance students’ Qur’anic reading abilities. A descriptive qualitative method was used, involving Qur’an teachers, students, and parents as participants, with data collected through observation, interviews, and documentation. The results indicate that two main strategies were implemented: the individual classical strategy and the repetition strategy. The individual classical strategy involves group learning sessions with direct correction of students’ recitations, while the repetition strategy focuses on repeated reading of verses to reinforce tajwid understanding and correct makhraj articulation. Both strategies have proven effective in gradually and comprehensively improving Qur’anic reading skills. These findings affirm that the success of Qur’anic reading instruction is strongly influenced by the active role of the Qur’an teacher and the use of adaptive and contextual approaches. The practical implication of this study suggests that appropriate strategies can foster the development of a Qur’anic generation equipped with both spiritual depth and technical proficiency in reading the holy text.